Agricultural extension capacity development in developing countries: an international training course at Michigan State University. Issue 3 (3rd April 2022) - Madan, Sunil; Baker, Anne; Maredia, Karim; Bates, Ronald
ABSTRACT: Purpose: The purpose of this paper is to share the initiatives of development and offering of an International Agricultural Extension training course by Michigan State University Extension (MSUE). MSUE is a global leader in agricultural research, education, and extension and actively shares knowledge and technologies worldwide. Design/Methodology/Approach: Owing to the COVID-19 pandemic, this in-person course rapidly transformed to an online one-week short course for global participants working in agricultural extension. Findings: There is a great demand for developing extension expertise and advisory services in line with the emergence of new tools and technologies. The use of ICT was at the forefront in sharing knowledge and disseminating technologies. Practical Implications: Several participants were interested in organising similar courses in their institutions and piloting some of the programmes that they learned. Theoretical Implication: The short course designed and offered during 2020 will be further enhanced and offered with a focus on outcome and responses received through a separate survey. Originality/Value: This paper focuses on the training and capacity building of the agricultural extension workers from developing countries and the US land-grant model of agricultural extension shared by MSUE.